Mewujudkan Sekolah Sehat melalui Optimalisasi Peran Jumantik dan Edukasi PHBS - Rokhmayanti, Rokhmayanti; Erviana, Vera Yuli; Wibowo, Rena Anjeli (CV. Rayyan Dwi Bharata, 2026)
Schools play an important role in increasing health awareness, including the implementation of Clean and Healthy Living Behavior (PHBS) to prevent diseases such as Dengue Fever (DBD). On February 3, 2025, the PHBS education program was implemented at Rasmisart School, Songkhla, Thailand, focusing on increasing teacher understanding and the role of Mosquito Larvae Monitors (Jumantik). The methods used included multimedia presentations and interactive discussions. Evaluation through pre-tests and post-tests showed an increase in understanding of 10%, with several aspects of PHBS reaching a level of understanding of 100%. These results confirm the effectiveness of PHBS education in increasing health awareness in the school environment. The methods used included multimedia presentations and interactive discussions. Evaluation through pre-tests and post-tests showed an increase in understanding of 10%, with several aspects of PHBS reaching a level of understanding of 100%. These results confirm the effectiveness of PHBS education in increasing health awareness in the school environment.